Prevalence and Risk Factors of Schistosomiasis among School-Age Children and Adolescents in Zaria, Kaduna State, Nigeria - Tanko A. Nanret; Suchi K. Nanret; Orinya Alfred; Ejembi Joan; Olanrewaju Jimoh; Dimowo C. Palangutde; Ahmed S. Opaluwa; Abdulaziz M. Mukhtar; Medugu Nubua (Darul Yasin Al Sys, 2026)
Nigeria carries the highest global burden of schistosomiasis, with prevalence and infection intensity particularly high among school-aged children and adolescents. In Zaria metropolis, the abundance of water bodies, irrigation farming, and recreational activities such as swimming may increase exposure to schistosomiasis transmission. This study aims to determine the prevalence and risk factors of schistosomiasis among school-aged children and adolescents in Zaria metropolis. A community-based cross-sectional study was conducted among participants aged 6–19 years. A multi-stage sampling technique was used to select communities, clusters, and households. Stool and urine samples were collected from eligible participants, and Schistosoma ova were identified using standard microbiological techniques. A questionnaire was used to obtain demographic profiles and data related to potential risk factors. Data were recorded and analyzed using SPSS version 26. A total of 423 participants were recruited from Biye, Bomo, Wuchichiri, and Kufena communities. The overall prevalence of schistosomiasis was 10.6% (45/423), comprising 9.5% (40/423) Schistosoma haematobium infection and 1.2% (5/423) Schistosoma mansoni infection. The identified risk factors for schistosomiasis were frequent contact with water through swimming and irrigation farming (AOR = 2.688, CI = 1.341–5.386, p = 0.005) and geographical location (AOR = 0.275, CI = 0.102–0.740, p = 0.011). The study concludes that schistosomiasis prevalence among school-aged children and adolescents in Zaria metropolis remains high, with transmission associated with geographical location and frequent contact with water bodies. These findings highlight the need for targeted prevention strategies, risk-reduction interventions, and public health education in communities with high exposure to water-related activities.